Pengaruh Karakteristik Dewan Direksi Terhadap Kebijakan Dividen Pada Bank Umum Syariah di Indonesia Periode Tahun 2011-2022 - Tazqy, Recha; Setiawan; Arshad, Destian (Journal of Applied Islamic Economics and Finance, 2024)
This study aims to determine the effect of board characteristics on dividend policy at Islamic commercial banks in Indonesia for the period 2011-2022. The method used is descriptive-quantitative using Stata MP 2017. The type of data used is secondary data. The purposive sampling method is used to identify 16 Islamic commercial banks in Indonesia that meet the criteria. The model chosen is REM (Random Effect Model). The hypothesis results show that the characteristics of the board of directors simultaneously have a significant effect on dividend policy. And partially shows that the variable size of the board of directors has a positive effect on dividend policy, the variable educational background of the board of directors has a negative effect on dividend policy, while the variable proportion of female directors, the variable age of the board of directors and the variable tenure of the board of directors have no effect on dividend policy.